All-Digital Timing Recovery for Free Space Optical Communication Signals With a Large Dynamic Range and Low OSNR - Yunfeng Gu; Sheng Cui; Changjian Ke; Keji Zhou; Deming Liu (IEEE Photonics Journal)
The free space optical communication (FSOC) signals often exhibit a much larger dynamic range and much lower OSNR than optical fiber communication signals, due to the large-scale relative motion of the terminals, change of atmospheric channel conditions and large transmission loss. For this reason flexible digital coherent receivers (DCR) capable of adapting to different channel conditions have attracted much attention in the FSOC field. As timing recovery is indispensable for DCRs, the development of a timing recovery algorithm (TRA) capable of processing such FSOC signals is of particular interest in FSOC field. In this paper we evaluate the performance of Gardner's timing error detector (TED) and propose a new blind TED with a lower computation complexity and more stable output characteristics. Based on the proposed TED, we design a feedback parallel TRA suitable for the FSOC signals and implement it in a FPGA to evaluate its real-time performance. Numerical simulations and experiments illustrate the merits of the proposed TRA based on new TED with respect to the TRA based on Gardner's TED.